2013
DOI: 10.1118/1.4819944
|View full text |Cite
|
Sign up to set email alerts
|

Mineralization in calcified plaque is like that of cortical bone—Further evidence from ultrashort echo time (UTE) magnetic resonance imaging of carotid plaque calcification and cortical bone

Abstract: CPC bears remarkable similarities with cortical bone in terms of BMD and T1. CPC shows a higher mean T2* and a lower mean water concentration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 48 publications
(69 reference statements)
0
9
0
Order By: Relevance
“…Thus, to completely replace the need for a planning CT, UTE MRI must be able to adequately depict these calcifications in the brain. It was recently shown that calcified arterial plaque appears very similar to cortical bone on UTE images, 40 which suggests that calcified brain lesions might be identifiable using the same techniques appropriate for cranial bone segmentation. In the present study, we could not acquire UTE MR images while the skull phantom was positioned in the MRgFUS system because our UTE pulse sequence was developed on a different MR scanner platform.…”
Section: Discussionmentioning
confidence: 98%
“…Thus, to completely replace the need for a planning CT, UTE MRI must be able to adequately depict these calcifications in the brain. It was recently shown that calcified arterial plaque appears very similar to cortical bone on UTE images, 40 which suggests that calcified brain lesions might be identifiable using the same techniques appropriate for cranial bone segmentation. In the present study, we could not acquire UTE MR images while the skull phantom was positioned in the MRgFUS system because our UTE pulse sequence was developed on a different MR scanner platform.…”
Section: Discussionmentioning
confidence: 98%
“…Specific MRI sequences, such as UTE, SWI, or DESS, were among the candidate items retained after item reduction, but in subsequent discussions were felt to be on the future research agenda for CPPD and not ready for routine clinical use nor for inclusion in CPPD classification criteria (24)(25)(26)42). Recently, UTE and SWI MRI have shown promise for the identification and quantification of calcium crystal deposition in and around joints as well as other anatomical sites (24,25,43,44).…”
Section: Discussionmentioning
confidence: 99%
“…However, recent advancement of MR technologies has enabled the application of ultrashort TE (UTE) MRI for routine clinical use. UTE MRI with 3D radial sampling of the free induction decay allows for the depiction of "solidstate" tissues or objects with very short T2 as bright signals, which help depict tendons, ligaments, menisci, [20][21][22] periosteum, 23 renal stones, 24 carotid plaque, [25][26] etc. Subtraction between two echoes during T2 decay makes the short T2 properties of the solid state stones more conspicuous.…”
Section: Introductionmentioning
confidence: 99%